Higher anaerobic digester performance by the strategical increase in the feeding rate of cow manure in laboratory continuous stirred tank reactor - Vahed Negahban; Mohammadali Ebrahimi-Nik; Abbas Rohani (PLoS ONE, 2025)
Improper management of dairy cow manure poses a major risk of environmental pollution. In contrast, anaerobic digestion provides a sustainable pathway by transforming manure into renewable biogas while reducing environmental burdens compared with conventional handling methods. This study examined the operational adaptation and performance of a continuous stirred-tank anaerobic digester fed with dairy cow manure, where the daily organic loading rate (kgVS/m³ reactor volume) was gradually increased to maximize biogas generation. The loading was progressively raised until clear signs of process instability appeared. The experiment was conducted over 98 days under mesophilic conditions, with pH maintained between 7.10 and 7.40. Initially, the digesters were supplied with 20 g of fresh manure per day (0.49 gVS/L), and the input was doubled weekly until reaching 280 g/day (6.82 gVS/L). Under optimal conditions, peak biogas and methane productions were 16.2 NL and 9.2 NL, respectively, corresponding to a maximum specific methane yield of 232 NL CH₄/gVS. The results show that higher loading rates stimulated microbial activity and accelerated organic matter degradation, leading to substantially greater biogas output. Moreover, the digestate exhibited improved physicochemical characteristics, enhancing its value as a nutrient-rich amendment for agricultural applications.